A Qualitative Analysis of Illicit Arms Trafficking on Darknet Marketplaces - Leonidou, Pantelitsa; Salamanos, Nikos; Farao, Aristeidis; Aspri, Maria; Sirivianos, Michael (My University, 2023)
During the last decade, the dark web has become the playground for criminal and underground activities, such as marketplaces of drugs and guns, as well as illegal content sharing. The dark web is one of the top crime environments presented in EUROPOL's Internet Organised Crime Threat Assessment 2021. This paper provides a qualitative study on the darknet marketplaces of illegal arms trafficking. For this purpose, we implemented a crawler based on the ACHE Python library to collect hidden web pages (onion services) on the Tor network. We gathered data from ten marketplaces recommended by dark web search engines - Ahmia, Deep Search, and Onion Land Search. We provide a first report of the overall landscape of illicit arms trafficking, discussing the range of weapons such as military drones, explosives, and other related products, together with the payment and shipping methods provided by the vendors. The findings verify previous reports from reputable institutions (United Nations and RAND Europe). Most of these illicit marketplaces are easily accessible to the average user; they are well-organized with a large variety of firearms and also provide extensive customer support.
Keywords: arms trafficking; black markets; dark web; darknet